X-ray CT images of IODP Hole 389-M0107A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Collection of X-ray Computed Tomography (CT) cropped orthogonal images along the core section splitting axis from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. X-ray CT imaging was conducted at the British Geological Survey Core Scanning Facility in Keyworth (UK) prior to the onshore phase in Bremen. The cores were scanned using a GEOTEK Rotating XCT (RXCT) core scanner and GEOTEK Reconstructor software for data and image processing. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025